Field Use of Protective Bacteriophages against Pectinolytic Bacteria of Potato - Petrzik, Karel; Vacek, Josef; Kmoch, Martin; Binderová, Denisa; Brázdová, Sára; Lenz, Ondřej; Ševčík, Rudolf (Microorganisms, 2023)
The pectinolytic Dickeya solani bacterium is an important pathogen found in potatoes. We conducted laboratory and field experiments mimicking severe and mild Dickeya spp. infection and investigated the application of a mixture of two lytic bacteriophages before and after bacterial infection to protect the plants. Application of the phage solution to tuber disks and wounded tubers did not completely eliminate the infection but reduced the development of soft rot symptoms by 59.5-91.4%, depending on the phage concentration. In the field trial, plants treated with bacteriophages after severe Dickeya infection had 5-33% greater leaf cover and 4-16% greater tuber yield compared to untreated plants. When simulating a mild infection, leaf cover was 11-42% greater, and tuber yield was 25-31% greater compared to untreated plants. We conclude that the phage mixture has the potential to protect potatoes ecologically from D. solani.
Keywords: Solanum tuberosum; biological control; Enterobacteriaceae; Limestonevirus